Tolerance and intolerance in religion and beyond: challenges from the past and in the present - Matviyets, Anne Sarah; Veltri, Giuseppe; Rüpke, Jörg (Routledge studies in religion, 2024)
This book focuses on religious tolerance and intolerance in terms of practices, institutions, and intellectual habits. It brings together an array of historical and anthropological studies and philosophical, cognitive, and psychological explorations by established scholars from a range of disciplines. Whilst the challenge of promoting tolerance has mostly been treated as a value or practice of demographic or religious majorities, this book offers a broader take and pays attention to minority perspectives. It is a valuable reference for scholars of Religious Studies, the Sociology of Religion and the History of Religion.